2012
DOI: 10.1111/j.1365-2311.2012.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg size and composition in an ageing capital breeder – consequences for offspring performance

Abstract: Abstract. 1. Egg size is often used as a proxy of egg quality although size and composition may vary, e.g. in insects egg size usually decreases as female ages. Whether this decrease in size reflects reduced concentrations of essential nutrients such as lipids and proteins of eggs laid by ageing females, or does reduced size per se explain often observed lower fitness of later laid eggs is poorly explored.2. Egg properties were compared with fitness parameters of offspring laid on the first and fourth night du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Alternatively, our results may simply indicate a nonadaptive physiological constraint. In other studies, authors have more commonly observed a gradual decrease in egg size, number and absolute provisioning over time in insects (Wiklund & Karlsson, ; Begon & Parker, ; Fox & Czesak, ; Geister et al ., ; Pöykkö & Mänttäri, ). Some have explained this trend as an unavoidable constraint of dwindling reproductive resources (Wiklund & Karlsson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, our results may simply indicate a nonadaptive physiological constraint. In other studies, authors have more commonly observed a gradual decrease in egg size, number and absolute provisioning over time in insects (Wiklund & Karlsson, ; Begon & Parker, ; Fox & Czesak, ; Geister et al ., ; Pöykkö & Mänttäri, ). Some have explained this trend as an unavoidable constraint of dwindling reproductive resources (Wiklund & Karlsson, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, P. astrigera females of the overwintering generation produced significantly larger eggs than the first generation. It is presumed that egg size is subject to selection, because it has substantial fitness effects on progeny (Pöykkö & Mänttäri, ). Because larger eggs yield larger offspring, mothers often lay larger eggs under stress conditions (Fischer, Bot, et al., ; Fischer, Brakefield, et al., ; Fischer et al., , ; Hassall, Walters, Telfer, & Hassall, ).…”
Section: Discussionmentioning
confidence: 99%
“…The 20 eggs per female measured for volume were used to estimate average amounts of protein (n = 96) and lipids (n = 101). Lipid content was analysed using a modified sulpho-phospho-vanillin method (Cheng et al, 2011;Pöykkö & Mänttäri, 2012). Egg protein analysis was done using the Bradford method (Bradford, 1976) in comparison with a bovine serum albumin standard.…”
Section: Egg Analysis and Fecundity In Gravid Femalesmentioning
confidence: 99%